Pengembangan LKPD Berbasis Generik Sains Menggunakan Limbah Sekitar Pada Materi Pokok Bahasan Koloid - Elmawati; Junaidi, Eka; Hadisaputra, Saprizal (Chemistry Education Practice, 2024)
This research is a research and development (R&D) that aims to find out: (1) the steps in the process of developing a generic science-based worksheet using ambient waste on colloid material (2) the level of validity and practicality of a generic science-based worksheet using ambient waste on colloid material regarding the water purification process that has been developed. The research design used 4D model (define, design, develop, and disseminate). The population in this study were all students of grade XI MIPA at SMA Negeri 1 Keruak, as many as 123 students and consisting of 4 classes. The sample used in this study was class XI MIPA-3 which consisted of 31 students. The results showed that the average validity value of the three validators for all aspects is 0.82 which indicates that the developed worksheet is in the very valid category. Meanwhile, practicality can be seen from student responses which show positive responses. The average percentage for all aspects is 85.2%, which indicates that the worksheets developed are in the very practical category. Based on these data, it can be concluded that the generic science-based worksheet using ambient waste on colloid material is valid and very practical to use in the learning process.